Chemical Characterization of Rural Organic Aerosol in the North China Plain Using Ultrahigh-Resolution Mass Spectrometry - Yun Zhang; Xu Gao; Xingang Hou; Mingyuan Liu; Jiajun Han; Hongyan Zhang (Atmosphere, 2023)
Atmospheric organic aerosol (OA) affects air quality and human health. However, compared with urban areas, the chemical composition and temporal distribution of OA in rural regions are still not well understood. In this study, one-year atmospheric particles with an aerodynamic equivalent diameter of ≤2.5 μm (PM2.5) were collected at a rural site in Quzhou County, the North China Plain (NCP), from August 2020 to July 2021. OA in PM2.5 samples were analyzed with an ultrahigh-performance liquid chromatograph (UHPLC) coupled to an ultrahigh-resolution Orbitrap mass spectrometer in negative mode (ESI−). The results show that the chemical composition and properties of OA varied in different seasons. According to the hierarchical cluster analysis, the molecular formulas of winter OA were close to those in spring, whereas the chemical composition of OA in summer and autumn was similar. The O/C ratio of summer OA was the highest at 1.21, followed by that in autumn (0.92) and spring (0.87), while the winter OA had the lowest O/C ratio of 0.64. It indicates that, compared to the other three seasons, OA underwent more intense oxidation processes in the summer. Moreover, winter OA contained more aromatic compounds with a relative peak abundance fraction of 40%, which may be related to anthropogenic sources (e.g., coal burning) in the winter in the NCP. In addition, biomass burning is considered an important source of OA in the rural region of Quzhou County, the NCP, in all seasons.